Desenvolvimento de fotoeletrodos baseados em filmes finos BVO para utilização em dispositivos na conversão de energia - Carmo, Éder José do (2020)
A photoelectrochemical cell (PEC) is a device capable of oxidizing organic matter from industrial waste, solar energy storage in chemical bonds in the form of H2, as well as generating electricity in a clean manner. Therefore, the use of this system becomes highly attractive as a potential substitute for fossil fuels. However, the efficiency of a PEC is largely determined by the crystalline phase of the involved material, which directly affects the photochemical properties and, therefore the capability for applications. The objective of the present work is to investigate the influence of deposition solution pH on thin films based on bismuth-vanadate-oxide (BVO). A photocatalyst was prepared by an alternative method and therefore deposited on the indium tin oxide (ITO) substrate by the spin-coating deposition technique, using three solutions defined as: M and A (with pH ≈ 2) and B (with pH ≈ 8). The microstructural properties, analyzed by scanning electron microscopy, revealed the formation of nanoporous islands with spongy morphology. From the structural properties, investigated by X-ray diffraction and Raman spectroscopy, the crystalline phases, atomic chemical bonds and their spatial position in the crystal structure were confirmed. On the other hand, the bandgap energy of the crystalline phases, obtained by diffuse reflectance spectroscopy, was found to be between 2.4 and 2.9 eV, meaning that the films can be excited under visible light. The photoelectrochemical performance of the electrodes was evaluated under light irradiation, showing higher photoactivity for the B photoelectrode, mainly in the anodic region, obtaining a photocurrent density of +74.6 μA/cm2 at 1.23 VERH, about 20 times larger compared to the M and A electrodes. These results reveal promising photoelectrochemical properties for the heterostructure formed on the B electrode, and their potential application in photoelectrochemical devices for renewable energy production.